Image-Based Dynamic Phenotyping Reveals Genetic Determinants of Filamentation-Mediated β-Lactam Tolerance - Zahir, Taiyeb; Wilmaerts, Dorien; Franke, Sabine; Weytjens, Bram; Camacho, Rafael; Marchal, Kathleen; Hofkens, Johan; Fauvart, Maarten; Michiels, Jan (Frontiers in Microbiology, 2020)
Antibiotic tolerance characterized by slow killing of bacteria in response to a drug can lead to treatment failure and promote the emergence of resistance. β-lactam antibiotics inhibit cell wall growth in bacteria and many of them cause filamentation followed by cell lysis. Hence delayed cell lysis can lead to β-lactam tolerance. Systematic discovery of genetic factors that affect β-lactam killing kinetics has not been performed before due to challenges in high-throughput, dynamic analysis of viability of filamented cells during bactericidal action. We implemented a high-throughput time-resolved microscopy approach in a gene deletion library of Escherichia coli to monitor the response of mutants to the β-lactam cephalexin. We computed the changes in frequency of lysed and intact cells due to the antibiotic action and uncovered several strains with atypical lysis kinetics. We show that strains can display filamented-mediated tolerance without being resistant, and therefore filamentation phenotype is not discernible through traditional antibiotic susceptibility methods. In tolerant filamented cells, antibiotic removal before lysis leads to an apparent burst of population growth due to numerous concurrent divisions. We find that deletion of Tol-Pal proteins TolQ, TolR or Pal but not TolA, TolB or CpoB leads to rapid killing by β-lactams. We also show that the timing of cell wall degradation determines the lysis and killing kinetics after β-lactam treatment. Altogether, this study uncovers numerous genetic determinants of hitherto unappreciated filamentation-mediated β-lactam tolerance, and support the growing call for considering antibiotic tolerance in clinical evaluation of pathogens. More generally, the microscopy screening methodology described here can easily be adapted to study lysis in large numbers of strains.